Arabic language script and encoding identification with support vector machines and rough set theory [electronic resource] - 281905 Mohamed Ould Mohamed Sidya; Ali Selamat, supervisor; Universiti Teknologi Malaysia. Fakulti Sains Komputer dan Sistem Maklumat (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2007